Unraveling the radiological enigma: ``Para testicular adenomatoid tumor masquerading as a triorchidism” A case report and literature review - Khalid Hussain, MBBS,MS; Rao Nouman Ali, MBBS, MRCPS, FCPS; Obaid Adil, MBBS, MS; Maria Khalid, MBBS, MS; Sohaib Irfan, MBBS, MD; Wajiha Irfan, MBBS, FCPS (Radiology Case Reports)
Paratestiular tumors are uncommon tumors in the vicinity of the testis with adenomatoid being the most common benign subtype. Adenomatoid tumors have a special predilection towards genital structures in both males and females. The epididymis is the most common site of occurrence of para-testicular adenomatoid tumors. These tumors show diversity in clinical presentation and most of the time remain inconclusive on ultrasonography and MRI. The radiological findings often mismatch with histopathological diagnosis. In our case, a young male of 28 years’ age presented with persistent pain in the scrotum, and on clinical examination a separate testis-like structure was observed. The radiological modalities were suggested as a case of triorchidism with the presence of a normal extra testis in the right scrotal sac. The surgical excision of the lump was done and sent to the histopathology department which revealed the occurrence of adenomatoid tumor hence clinicians should be aware of these clinical and radiological diversities of paratesticular adenomatoid masses and should be meticulous in managing patients with spurious scrotal masses.